Association of Systolic Blood Pressure Time in Target Range With Cardiovascular Events Among PRECISION Participants - Neel Agarwal; Julie St. John; Vikas Sunder; Ashish Sarraju; Luke J. Laffin (The Journal of Clinical Hypertension, 2025)
ABSTRACT Blood pressure (BP) is a dynamic vital sign with variability. Novel metrics that account for BP variability and longitudinal control are gaining interest, such as time in target range (TTR) assessments. TTR is the percentage of time a patient's BP is within a desired range. We sought to determine if systolic BP TTR was associated with major adverse cardiovascular events (MACE) among participants in the PRECISION (Prospective Randomized Evaluation of Celecoxib Integrated Safety versus Ibuprofen or Naproxen) trial. PRECISION was a 24 081‐participant cardiovascular (CV) outcomes trial comparing celecoxib, naproxen, or ibuprofen in participants with increased CV risk. Systolic BP was in the target range if it was between 110 and 130 mm Hg. TTR was determined via traditional and Rosendaal linear interpolation (RLI) methods. Participants were categorized based on TTR achieved, <25%, 25%–<50%, 50%–<75%, or ≥75%. Hazard ratios (HR) and Kaplan–Meier survival curves were generated. Twenty thousand four hundred and eighty‐seven participants had at least four BP readings available for analysis and a median follow‐up of 27.6 ± 5.4 months. The cohort had a mean baseline BP of 125.2 mm Hg and a mean systolic BP of 127.5 mm Hg when accounting for all follow‐up visits. A lower risk of MACE was observed among individuals with ≥75% TTR compared with those <25% using the traditional (adjusted HR 0.70, 95% CI 0.52–0.95, p = 0.02) and RLI method (adjusted HR 0.56, 95% CI 0.43–0.75, p < 0.001). More systolic BP TTR is associated with a lower risk of MACE among individuals in PRECISION.